ANALISIS DAN USULAN PENERAPAN KESELA MATAN DAN KESEHATAN KERJA DI PT.XYZ MAJALENGKA - Muhamad, Sholeman; Whydiantoro, Whydiantoro (Universitas Majalengka, 2019)
PT. XYZ Majalengka is a textile company that operates the demand for fabrics in its production process, the company thinks that quality human resources are important and needed, which is the reason why they implement occupational health and safety procedures with research that is preceded by interviews and documentary studies followed by data collection where data collection is carried out by taking several lists of the application of occupational safety and health, research shows there are several applications and proposals for the application of occupational safety and health including the application contained in PT. XYZ in the form of fire extinguisher, safety and health signs work and first aid box for workplace accidents. for proposals for the application of occupational safety and health itself in the form of signposts, namely: ear protection signs, use gloves, make sure the arrangement of items is neat, use masks, are prohibited from using cellphones and signs do not run around.